GE_GERICHTE P/25515/2023 vom 16. April 2025 - GE Cour de justice (2025)
MESURE DE CONTRAINTE(PROCÉDURE PÉNALE);REQUÊTE EXPLORATOIRE;NOM;SURVEILLANCE;MANDAT DE PERQUISITION;PREUVE ILLICITE;INDEMNITÉ(EN GÉNÉRAL) | LEI.115.al1.leta; LEI.115.al1.letb; LStup.19.al1; LStup.19.al2; LPol.47; CPP.197; CPP.158.al2; CPP.177.al3; CPP.141; CPP.429